Differences in the oral hygiene status and clinical periodontal status between conventional and electric smokers - Angguningtyas Wulandari; Sri Widiati; Bambang Priyono (Majalah Kedokteran Gigi Indonesia, 2022)
Conventional and electrical cigarette use could result in bad pathological conditions in the oral cavity, which may lead to periodontal diseases. This research aimed to determine the differences in the oral hygiene and clinical periodontal status between conventional and electric smokers. This research was a quantitative observational research and was designed as a cross-sectional study. The samples were selected using purposive sampling. A total of 110 respondents (n = 110) were involved, consisted of 60 conventional smokers and 50 electric smokers. Their oral hygiene status were examined using oral hygiene index simplified (OHI-S) measurement, while their periodontal tissue status were assessed using bleeding on probing (BOP) and probing pocket depth (PPD) measurements. The data were analyzed using the Mann-Whitney test with a significance level of α < 0.05. The median and first quartile of OHI-S scores of the conventional smokers’ group were 2.7 and 2.2, while the electric smokers’ group was 2.2 and 1.4 respectively, with a significant value of p < 0.001. The median and first quartile BOP scores of the conventional smokers’ group were 36% and 29%, while the electric smokers’ group were 35% and 28% respectively, with a significant value of p = 0.750. The median and first quartile of PPD scores in the conventional smokers’ group were 3.2 and 2.7, while the electric smokers’ group were 3.1 and 2.6 respectively with a significant value of p = 0.765. Conventional smokers had worse oral hygiene status than electric smokers. Conventional and electric smokers did not have significant differences in periodontal health including gingival bleeding and poor pocket depth.